Biliary complications in donation after circulatory death liver transplantation: the Australian National Liver Transplantation Unit's experience. Issue 3 (28th September 2020) - Ly, Mark; Crawford, Michael; Verran, Deborah
Abstract: Background: Biliary complications are the most common complications of donation after circulatory death (DCD) liver transplantation and the international experience with DCD transplants suggests increased rates of biliary complications compared to donation after brain death transplants. Therefore, it is important to understand factors that are associated with the development of biliary complications within the Australian DCD context in order to inform future practice. The aim of this study is to determine the incidence of biliary complications after DCD liver transplantation at the Australian National Liver Transplantation Unit and identify factors associated with this outcome. Methods: A retrospective analysis of all adult DCD liver transplants at the Australian National Liver Transplantation Unit from 2007 to 2015 was undertaken. The primary outcome measure was the incidence of biliary complications and was censored on 31 December 2016. Recipients were then stratified into groups based on the development of biliary complications and risk factor analysis was performed. Results: Biliary complications occurred in 35% of DCD transplants, including seven anastomotic strictures and 10 non‐anastomotic strictures. Higher donor risk index scores ( P = 0.03), post‐transplant portal vein complications ( P = 0.042) and peak gamma‐glutamyl transferase levels within 7 days post‐transplant ( P = 0.047) were associated with biliary complications. Conclusion: Findings from this study demonstrate that biliary complications remain common in DCD liver recipients. Recipients who developed a biliary complication tended to have higher donor risk index, elevated peak gamma‐glutamyl transferase levels within 7 days post‐transplant or a portal vein complication. The presence of any of these factors should prompt close monitoring for post‐transplant biliary complications. Abstract : Biliary complications are common in donation after circulatory death liver transplantation. A risk factor analysis was performed to identify features associated with biliary complications in this population within an Australian setting.